Identification Of Physical, Chemical and Microbiological Quality Of Snacks In Smart Park Samarinda City - Sri Evi Newyearsi Pangadongan; Apriyani; Istiarto; Iwan Harwidian Maharismas; Anisa Dinah; Steven (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Street food, according to the Food and Agriculture Organization (2019), is food and beverages served in containers sold on the side of the road or other places, which have been prepared or cooked at home or at the place of sale. Problems related to the use of food additives are one component of various nutritional problems in society, in addition to problems related to food shortages, poor handling, and processing. With the increasing enthusiasm of producers in producing food products that have high selling value, the use of food additives has increased. Research Objective. This study aims to identify the content of hazardous food additives (formalin, methanyl yellow, borax, rhodamine, and coliform bacteria contamination) in fast food around the Taman Cerdas area. Methods. This type of research is quantitative, using a pre-research design, the one-shot case study, with an analytic approach. The samples in this study were pentol, yellow wet noodles, otak-otak, and sauce sold in the Smart Park area of Samarinda City. Results. After observing 8 samples of snacks from physical quality, namely color, texture, and aroma, and the results of chemical quality tests, the results of the snacks were safe for consumption, while the results of the microbiological test found 7 samples of snacks were contaminated with coliform bacteria and 1 sample of snacks was not contaminated with coliform bacteria. Conclusion. Snacks in the Smart Park area of Samarinda City are physically and chemically safe because they do not contain hazardous materials. However, microbiological test results showed that 7 out of 8 samples were contaminated with coliform bacteria. This condition makes snacks not meet the standards of PMK No. 2 of 2023 and is at risk of causing digestive diseases, so it is hoped that the results of this study can be followed up by traders to maintain the importance of sanitation in serving snacks so that the snacks avoid contamination with coliform bacteria. Keywords: Snack Food, Physical Quality, Chemical Quality, Microbiological Quality